2022
DOI: 10.3390/su142114655
|View full text |Cite
|
Sign up to set email alerts
|

Self-Determination Theory and Online Learning in University: Advancements, Future Direction and Research Gaps

Abstract: Self-Determination Theory (SDT) has been studied to comprehend human motivation, particularly in education. Numerous studies have been conducted at universities regarding online learning as a technology to mitigate the effects of COVID-19. On the basis of these expansions, however, there is a knowledge gap regarding what constitutes advancement, future direction, and research gaps regarding SDT in university online learning. This new systematic literature review analyzed 49 articles using PRISMA to bridge the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…From the perspective of SEVT and SDT, learning motivation comes from internal drives and external stimuli; therefore, the four-factor structural model more accurately captures students' intrinsic and extrinsic aspects of science learning compared to the three-factor structural model. The results also echoed the need for theory integration (Rosli et al, 2022) [57]. Prior TIMSS motivation studies have also separated the intrinsic value and utility value when examining the relationship between students' motivation and science achievement (e.g., Lay and Chandrasegaran, 2016;Liou et al, 2020;and Wang and Liou, 2017) [11,17,58] and found that the strength of the two task values were different in predicting the outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…From the perspective of SEVT and SDT, learning motivation comes from internal drives and external stimuli; therefore, the four-factor structural model more accurately captures students' intrinsic and extrinsic aspects of science learning compared to the three-factor structural model. The results also echoed the need for theory integration (Rosli et al, 2022) [57]. Prior TIMSS motivation studies have also separated the intrinsic value and utility value when examining the relationship between students' motivation and science achievement (e.g., Lay and Chandrasegaran, 2016;Liou et al, 2020;and Wang and Liou, 2017) [11,17,58] and found that the strength of the two task values were different in predicting the outcomes.…”
Section: Discussionmentioning
confidence: 60%
“…In the online learning context, the theory suggests that students who feel autonomous in their learning process, connected to others in their online learning community, and competent in their online learning skills are more likely to be motivated and engaged in their online learning experience [20,21]. SDT is suitable for the present study for several reasons.…”
Section: Introductionmentioning
confidence: 99%
“…First, SDT provides a theoretical framework for understanding students' motivations for adopting online learning during a crisis situation, such as the COVID-19 pandemic, by highlighting the role of personal autonomy and competence in promoting engagement and well-being. Second, SDT has been widely tested and validated in various educational settings and has been found to be a strong predictor of students' engagement and academic performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by meeting students’ basic psychological needs in the classroom, teacher can create an enjoyable setting to intrinsically motivate students to participate in learning activities, providing positive experience that empower foreign language learning ( Dincer et al, 2019 ). The SDT’s constructs are also applied to the digital technologies’ research field in education ( Chen and Zhao, 2022 ; Rosli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%